PENGARUH GOOD CORPORATE GOVERNANCE (GCG) DAN LEVERAGE TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN SEKTOR BARANG KONSUMEN PRIMER - Ayu Fatmawati; Rudiyanto; Firda Mufidah (The Asia Pacific Journal Of Management Studies, 2024)
This study aims to explain the empirical evidence regarding the effect of Good Corporate Governance (GCG) and leverage on financial performance in Primary Consumer Goods Sector Companies listed on the Indonesia Stock Exchange for the period 2018-2021. This study uses secondary data such as financial reports, company annual reports, and other related information regarding primary consumer goods sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2018-2021. The population used in this study were 105 companies. Based on the criteria set, a sample of 36 companies was obtained with a total observation data of 108 data. The method used in this research is to use quantitative methods. And the sampling technique uses purposive sampling technique. In this study using multiple linear regression methods using the SPSS 25 program to see the effect of each variable. The results of this study prove that Institutional Ownership partially has no effect on financial performance. The Board of Directors partially affects financial performance. The Audit Committee partially has no effect on financial performance. Leverage partially affects financial performance. The results of the simultaneous test state that the variables of Institutional Ownership, Board of Directors, Audit Committee and Leverage simultaneously affect Financial Performance.